2017
DOI: 10.3389/fimmu.2017.00079
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of GvHD and Other HSCT-Related Major Complications

Abstract: For over 60 years, hematopoietic stem cell transplantation has been the major curative therapy for several hematological and genetic disorders, but its efficacy is limited by the secondary disease called graft versus host disease (GvHD). Huge advances have been made in successful transplantation in order to improve patient quality of life, and yet, complete success is hard to achieve. This review assimilates recent updates on pathophysiology of GvHD, prophylaxis and treatment of GvHD-related complications, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
171
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(179 citation statements)
references
References 129 publications
(154 reference statements)
3
171
0
5
Order By: Relevance
“…H ematopoietic stem cell transplantation (HSCT) has been used for decades to treat a wide range of hematological malignancies, such as acute myeloid leukemia (AML) (1). Although its efficacy has evolved in the last years, the procedure is still associated with substantial transplant-related morbidity, mainly underlying disease relapse, graft-versus-host disease (GvHD), and infections (2). To improve transplantation outcomes, the impact of donor graft T cell subsets on the clinical outcome after HSCT has been studied.…”
mentioning
confidence: 99%
“…H ematopoietic stem cell transplantation (HSCT) has been used for decades to treat a wide range of hematological malignancies, such as acute myeloid leukemia (AML) (1). Although its efficacy has evolved in the last years, the procedure is still associated with substantial transplant-related morbidity, mainly underlying disease relapse, graft-versus-host disease (GvHD), and infections (2). To improve transplantation outcomes, the impact of donor graft T cell subsets on the clinical outcome after HSCT has been studied.…”
mentioning
confidence: 99%
“…The development of GVHD after the injection of histoincompatible BM is associated with the development of autoimmune disease, that is, with the presence of the autoreactive clone of T-effector cells, which are differentiated from donor hematopoietic stem cells in the recipients' body [2]. Experimental models of GVHD showed that donor effector T-cells attack various tissues of the recipient's body, including the thymus, destroying its architectonics, which leads to thymic involution and lymphopenia [30,31].…”
Section: Determination Of the Number Of Foxp3 Gene Transcripts In сD4mentioning
confidence: 99%
“…A serious disadvantage of transplantation of histoincompatible bone marrow (BM) in clinic is the development of acute or chronic form of the «graft-versus-host» disease (GVHD) in a recipient [1,2]. At present, a variety of approaches to recipient support or bone marrow (BM) treatment to remove T-lymphocytes that are responsible for the GVHD are used to prevent or minimize the development of this pathology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Damage to the gastrointestinal (GI) mucosa in patients undergoing HSCT is a serious but still poorly understood complication. Toxicity of HSCT conditioning regimens and graft-versus-host disease (GvHD) result in a 5-fold increase of the risk of significant GI complications compared with other cancer survivors [1,2]. Chemotherapy and total body irradiation (TBI) can damage GI mucosa and cause diffuse inflammation of GI tract.…”
Section: Introductionmentioning
confidence: 99%